Sugar Variation in Soybean Seed Assessed with a Rapid Extraction and Quantification Method - A. Hou; P. Chen; A. Shi; B. Zhang; Y.-J. Wang (International Journal of Agronomy)
Sugar content in soybean [Glycine max (L) Merr.] seed is an important quality attribute for soyfood and feed. Rapid extraction and quantification of soluble sugars in soybean seed are essential for large-scale breeding selections. In this study, using water as extractant combined with a high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) system, variability and repeatability of sugar content were tested in 20 diverse soybean genotypes. Individual sugars were clearly resolved and identified, including sucrose, stachyose, raffinose, glucose, fructose, and verbascose. Analysis of variance (ANOVA) revealed a highly reproducible estimation of sucrose, stachyose, and raffinose. PI 243545 was confirmed as a unique germplasm with the highest sucrose (105.48 mg/g) and total sugar (148.76 mg/g) content. Two low-oligosaccharide accessions, PI 200508 and 03CB-14, were confirmed with extremely low concentrations of raffinose and stachyose. PI 417559 was identified as a high glucose and fructose germplasm. The identified germplasm with unique sugar profiles will be valuable in breeding specialty soybeans for improved sugar content. The sugar testing method will facilitate the screening of seed sugar profiles in a large-scale soybean breeding program.